Practical large scale antenna systems for 5G cellular communications - Rowell, C.; Han, S. (Nazarbayev University, 2014)
In order to increase capacity and reduce power consumption for future cellular networks, new cellular architectures and radio access schemes will be required. Two important technologies for future 5G networks include Cloud-Radio Access Networks (C-RAN) [1] and Large Scale Antenna Systems (LSAS) with hundred's of low power radios to increase the cell capacity with multi-user MIMO multiplexing and beamforming. Although LSAS in theory [2] promises large capacity gains at the fraction of the power consumed by the current macro-basestations; there are many practical challenges that need to be overcome before LSAS can be successfully integrated into current and future cellular networks including: 1) low-power beamforming algorithms and 2) irregular array beamforming. This project examines each challenge and proposes possible solutions.
Keywords: cellular; cellular communications; radio; scale antenna systems; beamforming; project